SOCIAL ASPECTS OF SUBSIDIZED FOREST PLANTATIONS IN THE STATE OF ESPÍRITO SANTO, BRAZIL - Canto, Juliana Lorensi do (2015)
This study was developed using information obtained from 71 farm owners, who were responsible for 92 contracts of subsidized forest plantation in the Espírito Santo State. The contracts were distributed in five areas, according to the place of delivering wood. The objective was to survey social aspects of the farms and the farm owners with subsidized forest plantations in the State. The sample of contracts represented about 88% of the total contracts finalized between October 2004 and October 2005, and it was stratified by area. Differences were verified among the five areas, in relation to the farms, farm owners and contracts. Farms ranged between 7.5 and 3000 ha, and 40.9% of them had between 100 and 300 ha. The subsidized forest plantations ranged between 1.5 and 100 ha, and 84.8% of them had up to 30 ha. Coffee plantation was the main productive activity of the farms, and 73.2% of the farm owners declared themselves as a farmer regarding to their main occupation.